Valladolid: City Wine Festival - Matellanes Lazo, Mónica (2012)
Some cities in the world have seen the advantages of Enological-enoturism’s activities. Valladolid city try to achieve a market positioning as an ideal metropolis to be an enological, culture destiny and city of wine event festival. The research pretends to show the wine sector and enological-tourism to many people with a spectacular and interactive way. It pretends to value Valladolid as a city able to develop enological-tourism’s activities in the world. For that we contacted with professionals of the area to obtain arguments and answers about Valladolid as a city of wine festival. The results explain that Valladolid is good for doing these activities and to be considered a city of wine.